Preoperative facet joint arthropathy does not impact long-term clinical outcomes after lumbar-stability-preserving decompression and dynesys fixation - Po-Hsin Chou (Nature Portfolio, 2021)
Abstract To evaluate the impact of the preoperative severity of facet joint arthropathy on long-term functional outcomes and spinopelvic parameters in patients undergoing lumbar-stability-preserving decompression and Dynesys fixation. In this retrospective study, 88 patients undergoing combined surgery at our hospital from 2008 to 2015 were included. The patients were divided into two groups, the less and more than mean degeneration groups, based on preoperative facet joint arthropathy of the index level(s). The clinical outcomes were the Visual Analogue Scale (VAS) score, the Oswestry Disability Index (ODI) score and spinopelvic parameters. The mean follow-up durations for the less and more than mean degeneration groups were 84.83 ± 27.58 and 92.83 ± 20.45 months, respectively. The combined surgery significantly improved VAS and ODI scores, and increased sacral slope (SS) regardless of preoperative arthropathy severity. In addition, facet joint arthropathy at adjacent levels continued to worsen after surgery in both arthropathy severity groups. Preoperative facet joint arthropathy did not influence most long-term clinical outcomes in patients undergoing lumbar-stability-preserving decompression and Dynesys fixation. This combined surgery may be suitable for patients with facet joint arthropathy regardless of disease severity.